Decision Making: Definition and Research traditions - Šarkutė, Ligita (Sociologija. Mintis ir veiksmas, 2009)
This article aims to analyse the process of decision making which is the object of interdisciplinary research. The definition of decision making is presented and the stages, limitations and simplification strategies of decision making are also discussed. This paper also deals with the scientific disciplines which examines decision making and with research paradigms widely used in decision making analysis. These paradigms are rational decision making and naturalistic decision making. The article also gives an overview of approaches to understanding decision making from the point of sociology.